2022
DOI: 10.2478/eoik-2022-0021
|View full text |Cite
|
Sign up to set email alerts
|

Customer churn prediction model: a case of the telecommunication market

Abstract: The telecommunications market is well developed but is characterized by oversaturation and high levels of competition. Based on this, the urgent problem is to retain customers and predict the outflow of customer base by switching subscribers to the services of competitors. Data Science technologies and data mining methodology create significant opportunities for companies that implement data analysis and modeling for development of customer churn prediction models. The research goals are to compare different a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
0
1
0
Order By: Relevance
“…They concluded that ensemble way achieves much better results compared to using single classifier. A different example from industry is the recent work done by Fareniuk et al [11]. The author used LSTM to predict the next steps for current customers, assigning a probability to each step that would predict which helps in expecting customer churn and consequently prevent it.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that ensemble way achieves much better results compared to using single classifier. A different example from industry is the recent work done by Fareniuk et al [11]. The author used LSTM to predict the next steps for current customers, assigning a probability to each step that would predict which helps in expecting customer churn and consequently prevent it.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The author used LSTM to predict the next steps for current customers, assigning a probability to each step that would predict which helps in expecting customer churn and consequently prevent it. Fareniuk et al [11] is 2022 used different data science and machine elarning models like k-nearest neighbor (KNN), NNs, and RF to classify the customers to loyal and likely to be churn for telecom companies using Ukrainian telecom company dataset and they achieved classification accuracy rate of 90%. Nguyen et al [12] in the same year, used the kernel SVM to predict customer's churn for telecom companies and they achieved a classification accuracy rate of 98.9%.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For the development of the present research, the results of related works were reviewed in order to identify the relevant methodology for this type of casuistry, being CRISP-DM, the one that not only raises in one of its phases the procedure for the prediction model, but also evaluates the business context, as highlighted by (Fareniuk, Y., 2022), as well as the importance of the deployment of an interface that allows, with a simple language, to present the scenarios, so that the user can define a correct strategy for customer retention, as stated in .…”
Section: Literature Reviewmentioning
confidence: 99%
“…In return, over a specific time span, a company faces a huge loss of its fan followings [6]. Because it is much more expensive to attract more customers than retain loyal customers [7]. The strategy of loyal customer retention plays a vital role in a company's growth.…”
Section: Introductionmentioning
confidence: 99%